Rural-urban disparities in cervical cancer screening uptake and its predictors among women aged 30–49 years in Ghana: a multivariate decomposition analysis - Prince Tsekpetse; Samuel Salu; David Mensah Otoo; Joy Flora Dushime; Joshua Shiuma; Betty Oloo; Bright Opoku Ahinkorah (BMC Women's Health)
Abstract Background Despite the high morbidity and mortality associated with cervical cancer in Ghana, screening uptake remains alarmingly low. Rural–urban disparities exist in screening uptake among women aged 30–49 years, a priority group for cervical cancer screening according to the World Health Organisation guidelines. This study examined rural–urban disparities in cervical cancer screening uptake and its predictors among women aged 30–49 years. Methods We analysed secondary data from the 2022 Ghana Demographic and Health Survey, comprising 7,105 women aged 30–49 years. A multivariate non-linear decomposition analysis was conducted to examine factors explaining rural–urban disparities in cervical cancer screening uptake. Furthermore, bivariate and multivariable logistic regression analyses were performed to identify predictors of screening uptake. Results Cervical cancer screening uptake was higher among urban women (9.66%) [n = 335/3,471; 95% CI: 8.15–11.41] than rural women (4.12%) [n = 150/3,634; 95% CI: 3.30–5.14]. Approximately 92% of the rural–urban disparity in cervical cancer screening uptake was attributable to differences in education, household wealth and media exposure. Among rural women, higher cervical cancer screening uptake was associated with older age (45–49 years; AOR = 2.11; 95% CI: 1.20–3.70), higher educational attainment (AOR = 11.78; 95% CI: 6.38–21.78), and frequent health facility visits (AOR = 2.19; 95% CI: 1.21–3.98). Among urban women, cervical cancer screening uptake was significantly associated with higher educational attainment (AOR = 3.03; 95% CI: 1.48–6.23) and being in the highest wealth index (AOR = 5.47; 95% CI: 1.34–22.33). Conclusion Cervical cancer screening uptake remains significantly lower among rural women compared to urban women in Ghana. The rural-urban disparities in cervical cancer screening uptake were largely due to differences in socio-demographic, socio-economic and behavioural characteristics. Key predictors of cervical cancer screening uptake included older age, higher education levels, more frequent visits to health facilities, and belonging to wealthier households. These findings underscore the need for targeted interventions, such as mobile screening units, community-based education, enhanced media campaigns, and subsidising the cost of cervical cancer screening, to address access barriers and improve equitable uptake across rural and urban settings.